Land Management Rights by The Government For Investment Needs in Indonesia - Permadi, Iwan (Universitas Islam Malang, 2023)
Management rights are considered to be one of the Government's efforts to facilitate large entrepreneurs in investing in Indonesia. Of course, investment is expected to improve the community's economy. One of the efforts to improve the economy is done by creating jobs for the community. So it is necessary to map the land that is ready for business activities for investors. This article focuses on land management rights by the government for investment needs in Indonesia. The results show that the Management Rights (HPL) arrangement is not explicitly spelled out in Law Number 5 of 1960 concerning Basic Agrarian Regulations. that management rights are not purely from the state's control rights over land, but rather the delegation of the state's control rights to the subject or holder of management rights. The concept of a land bank in terms of its function becomes very important to consider as an instrument for land reserves in investment efforts for the prosperity of the people.